Educational video for parents about devices in the postoperative period of pediatric cardiac sugery (Research, Society and Development, 2025)
This methodological study aimed to create an educational video for parents and caregivers, explaining the medical devices used in children during the postoperative period of cardiac surgery in a pediatric and neonatal intensive care unit. The methodology followed Falkembach's framework, encompassing the stages of analysis and planning, modeling, and implementation. The video was developed using a playful and interactive approach, employing animated explanations of medical devices to facilitate family members' understanding. The educational video proved to be an effective strategy for welcoming and educating caregivers about medical devices. This educational technology improved communication and caregiver autonomy; however, the lack of impact assessment limits the analysis of its effectiveness. The study reinforces the role of nurses as educators and encourages the use of videos in humanizing care.